2021
DOI: 10.1002/mrm.28738
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution head and neck MRA using deep machine learning

Abstract: To probe the feasibility of deep learning-based super-resolution (SR) reconstruction applied to nonenhanced MR angiography (MRA) of the head and neck. Methods: High-resolution 3D thin-slab stack-of-stars quiescent interval sliceselective (QISS) MRA of the head and neck was obtained in eight subjects (seven healthy volunteers, one patient) at 3T. The spatial resolution of high-resolution ground-truth MRA data in the slice-encoding direction was reduced by factors of 2 to 6. Four deep neural network (DNN) SR rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…19 The successful application of superresolution was previously demonstrated in head and neck and knee imaging as well as in precontrast and postcontrast abdominal MRI. 19,31,32 The novelty of the presented algorithm in our study consists especially of the partial omission of the acquired data with slight reduction of acquisition time and, therefore, reduction of breath-holds including possible mitigation of motion of the intestine or diaphragm leading to an increase in sharpness. Breathing artifacts are still one of the most significant impairments in GRE imaging of the upper abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…19 The successful application of superresolution was previously demonstrated in head and neck and knee imaging as well as in precontrast and postcontrast abdominal MRI. 19,31,32 The novelty of the presented algorithm in our study consists especially of the partial omission of the acquired data with slight reduction of acquisition time and, therefore, reduction of breath-holds including possible mitigation of motion of the intestine or diaphragm leading to an increase in sharpness. Breathing artifacts are still one of the most significant impairments in GRE imaging of the upper abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to simple denoising algorithms, super-resolution aims to increase the spatial resolution via DL-based post-processing [ 40 , 41 , 42 ]. This concept was successfully implemented in head and neck imaging, as well as abdominal and cardiac imaging [ 40 , 43 , 44 ]. Especially fast sequences, such as gradient echo (GRE) imaging, benefit from these implementations, due to their relatively low signal-to-noise ratios.…”
Section: Deep Learning Applications In Radiologymentioning
confidence: 99%
“…It was shown that a DNN was efficient as a super-resolution method for musculoskeletal images 97 and MR angiography (MRA). 98…”
Section: Deep Learning and Its Applicationsmentioning
confidence: 99%